High-entropy iron-manganese-based transition metal layered oxide positive electrode material and preparation method and application thereof

The development of titanium-doped high-entropy iron-manganese-based transition metal layered oxide positive electrode material through high entropy strategy solved the problem of insufficient performance of the positive electrode material of sodium ion battery and achieved the effect of high energy density and long cycle life.

CN119503904APending Publication Date: 2025-02-25NORTHEASTERN UNIV AT QINHUANGDAO
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411679711.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The application of sodium ion batteries faces the problems of low energy density, short cycle life and poor stability, especially the insufficient performance of the positive electrode material, which affects the overall performance of the battery.

Method used

The high entropy strategy was adopted to develop a titanium-doped high-entropy iron-manganese-based transition metal layered oxide cathode material, and the high structural stability and excellent electrochemical properties of the material were obtained through specific synthesis methods.

Benefits of technology

High reversible capacity and excellent cycle stability are achieved, electrochemical performance is improved, and material preparation costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503904A_ABST
    Figure CN119503904A_ABST
Patent Text Reader

Abstract

The invention relates to a high-entropy iron-manganese-based transition metal layered oxide positive electrode material and a preparation method and application thereof, and belongs to the technical field of sodium ion batteries, and the preparation method comprises the following steps: dissolving an iron source, a copper source, a manganese source and a nickel source in an aqueous solution of ethanol and ethylene glycol to form a first solution; dissolving a precipitator in an aqueous solution of methanol and ethanol to form a second solution; heating a methanol solution in an oil bath, dropwise adding the first solution and the second solution, introducing Ar and H2, adjusting the pH value of the solution, reacting, standing and aging, carrying out solid-liquid separation, washing and drying a product, fully mixing and grinding the product with a sodium supplementing agent, titanium dioxide and an organic solvent, heating in Ar and N2, cooling and rapidly grinding to obtain the positive electrode material. The method is simple in process, good in controllability, cheap in raw material and wide in raw material source, the prepared material is uniform in particle size, uniform in distribution and high in crystallinity, the electronic and ionic conductivity of the material is improved, high reversible capacity and excellent cycling stability are obtained, the cost is reduced, and meanwhile the electrochemical performance of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and specifically relates to a high-entropy iron-manganese-based transition metal layered oxide positive electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, the field of electrochemical energy storage has developed rapidly, and is committed to the research and development of high-capacity, high-energy-density and high-safety batteries. Although lithium-ion batteries (LIBs) have been popular in the energy storage market for decades, the lack of lithium resources, dependence on imports, high costs and safety issues have caused increasing concerns and seriously hindered their further application in large-scale energy storage systems. Sodium-ion batteries (SIBs) have a similar working mechanism to lithium-ion batteries and are considered to be a promising alternative to LIBs due to their cost-effectiveness and natural abundance. However, the application of sodium-ion batteries still faces the problems of low energy density, short cycle life and poor stability. Among them, the positive electrode material has an important influence on improving battery performance. Solving the positive electrode material is to solve the problem of popularization of sodium-ion batteries. Therefore, the development of high energy density and excellent cycle stability positive electrode materials is the key to the innovation of sodium electricity.

[0003] Transition metal oxide materials have the advantages of simple synthesis, adjustable composition, and high power density. Layered transition metal oxide materials, with the general formula of Na x MeO2, where Me is a transition metal site. The metal elements of 100% of the transition metal sites of layered transition metal oxide materials can be adjusted, which provides great convenience for the chemical composition design of iron-manganese-based positive electrode materials. Specifically, according to the different sodium ion content in the structure, it can be divided into sodium-poor tunnel-type transition metal oxides, medium sodium-content P2 phase transition metal oxides and sodium-rich O3 phase transition metal oxides. Among them, the stoichiometric ratio of the O3 phase oxide is close to 1, and the sodium-rich phase structure gives the material a higher initial capacity, which is considered to be one of the most promising positive electrode materials for sodium ion batteries. However, this type of compound has obvious disadvantages: this material undergoes complex phase changes during the reaction, which will lead to a decrease in the cyclic stability of the material. Therefore, how to stabilize the structure of the O3 phase transition metal oxide material during the charge and discharge process is particularly important. The high entropy strategy is regarded as an effective structural stabilization strategy. When the configurational entropy in the transition metal oxide material is greater than 1.5R, it can be called a high entropy metal oxide. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a method for preparing a titanium-doped high-entropy iron-manganese-based transition metal layered oxide positive electrode material. The synthesis method has a simple process and good controllability. The raw materials are cheap and widely available. The obtained material particles have uniform particle size, uniform distribution, and high crystallinity, which improves the electronic and ionic conductivity of the material, obtains high reversible capacity and excellent cycle stability, thereby reducing the cost of material preparation and improving the electrochemical performance of the material.

[0005] The technical solution adopted by the present invention to solve the above technical problems is:

[0006] A method for preparing a high entropy iron-manganese-based transition metal layered oxide positive electrode material comprises the following steps:

[0007] (1) dissolving an iron source, a copper source, a manganese source and a nickel source in an aqueous solution of ethanol and ethylene glycol in a ratio of 2:2:3:2 of the sum of the molar amounts of all components to form a first solution; dissolving a sodium-containing precipitant in an aqueous solution of methanol and ethanol to form a second solution;

[0008] (2) transferring the methanol solution to a reaction vessel and heating it in an oil bath; three ports are provided on the top of the reaction vessel; hydrogen and argon reaction stabilizing protective gas is introduced into the first port of the reaction vessel; the first solution is added dropwise to the reaction vessel through the second port; the second solution is added dropwise to the reaction vessel through the third port; magnetic stirring is turned on, and the pH value of the solution is adjusted at the same time; after the first solution and the second solution are added dropwise, stirring is performed in an oil bath to obtain an orange-yellow solution;

[0009] (3) The obtained orange-yellow solution is allowed to stand for aging, and then centrifuged and solid-liquid separated. The obtained centrifugal precipitate is washed with water and then with anhydrous ethanol; the washed precipitate is vacuum dried at 110±5° C. to obtain a precursor, i.e., MNCF carbonate precipitate;

[0010] (4) fully mixing and grinding the prepared MNCF carbonate precipitate with a sodium supplement, titanium dioxide and an organic solvent, and performing ultrasonic stirring to obtain a mixture;

[0011] (5) The mixture in the above step (4) is heated under nitrogen and argon anti-oxidation protective gas, cooled in the furnace and then quickly ground to obtain a titanium-doped high-entropy iron-manganese-based transition metal layered oxide positive electrode material, denoted as Na 0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe 0. 2Ti 0.1 O2.

[0012] in:

[0013] In the step (1), the iron source is a mixture of FeSO4·7H2O and Fe(NO3)3·9H2O, and the molar ratio of FeSO4·7H2O to Fe(NO3)3·9H2O is (1-2.15):1.

[0014] In the step (1), the copper source is a mixture of Cu(NO3)2·3H2O and CuCl2·2H2O, and the molar ratio of Cu(NO3)2·3H2O to CuCl2·2H2O is (1-1.6):1.

[0015] In the step (1), the manganese source is a mixture of Mn(NO3)2·4H2O and MnSO4·H2O, and the molar ratio of Mn(NO3)2·4H2O to MnSO4·H2O is (1.15-1.32):1.

[0016] In the step (1), the nickel source is a mixture of Ni(NO3)2·6H2O and NiSO4·6H2O, and the molar ratio of Ni(NO3)2·6H2O to NiSO4·6H2O is (1-2.4):1.

[0017] In the step (1), the sodium-containing precipitant is a mixture of Na2CO3, NaHCO3 and CH3COONa, and the molar ratio of Na2CO3, NaHCO3 and CH3COONa is (2-6.5):(0.145-0.15):0.1; the molar ratio of the added amount of the sodium-containing precipitant to the total amount of metal elements added to the iron source, copper source, manganese source and nickel source is (1.55-1.8):1.

[0018] In the step (1), the concentration of the iron source in the first solution is 0.44 mol / L, and the concentration of sodium ions in the sodium-containing precipitant in the second solution is 4.15 mol / L to 4.7 mol / L.

[0019] In the step (1), in the aqueous solution of ethanol and ethylene glycol, the molar ratio of ethanol, ethylene glycol and water is (0.2-1):(0.2-1):10.

[0020] In the step (1), in the aqueous solution of methanol and ethanol, the molar ratio of methanol, ethanol and water is (0.2-0.6):(0.2-0.6):10.

[0021] In the step (2), the oil bath temperature is 60±1° C., the stirring time is 10 h to 14 h; the dropping rate of the first solution and the second solution is 200 μL / min to 500 μL / min, and the pH range is 8 to 8.2.

[0022] In the step (2), the hydrogen-argon reaction stabilizing shielding gas is a mixed gas of Ar and H2, and the volume ratio of Ar to H2 is (19-49):1.

[0023] In the step (2), the molar ratio of methanol to water in the methanol solution is (0.2-0.5):10.

[0024] In the step (2), the volume ratio of the first solution, the second solution and the methanol solution is 2:3:10.

[0025] In the step (3), the orange-yellow solution is allowed to stand for 3 to 6 hours, the centrifugal speed is 7000 to 9000 r / min, and the centrifugal time is 4 to 7 minutes; the vacuum drying time of the washed precipitate is 10 to 18 hours.

[0026] In the step (4), the sodium supplement is a mixture of NaNO3 and NaCl, and the mass ratio of NaNO3 to NaCl is (4-6):1.

[0027] In the step (4), the mass ratio of MNCF carbonate precipitate, sodium supplement and titanium dioxide is (14-15): (10.95-11.1):1.

[0028] In the step (4), the organic solvent is a mixture of acetone, ethanol and toluene, and the volume ratio is 1:1:(0.05-0.1).

[0029] In the step (4), the ratio g:L of the total mass of the MNCF carbonate precipitate, the sodium supplement and titanium dioxide to the volume of the organic solvent is (90-92.8):1.

[0030] In the step (4), the ultrasonic stirring is specifically, ultrasonic dispersion for 1 h to 3 h, followed by strong magnetic stirring for 8 h to 14 h.

[0031] In the step (5), the nitrogen-argon anti-oxidation protective gas is a mixed gas of Ar and N2, and the volume ratio of N2 to Ar is (3-4):1.

[0032] In the step (5), the heating process is specifically as follows: heating to 400°C to 550°C at a heating rate of 5°C / min to 8°C / min, keeping the temperature for 4 to 5 hours, and then heating to 850 to 900°C, keeping the temperature for 10 to 13 hours.

[0033] A high entropy iron-manganese-based transition metal layered oxide positive electrode material, specifically Na 0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe 0.2 Ti 0.1 O2, prepared by the above preparation method.

[0034] The application of the sodium ion battery layered oxide positive electrode material comprises the following steps:

[0035] The sodium ion battery high entropy iron-manganese-based transition metal layered oxide positive electrode material Na 0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe 0.2 Ti 0.1 O2 was used as the electrode material of the sodium ion battery, and the metal sodium sheet was used as the counter electrode. A CR2025 button-type sodium ion battery was assembled in a glove box filled with argon gas, and the charge and discharge cycle was performed in the potential range of 2 to 4.2 V. At a current of 1C, the first reversible specific capacity was 103 to 110 mAh / g, and the capacity retention rate reached 70% to 90% after 100 cycles.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] 1. The entropy-stabilized layered transition metal oxide cathode material was constructed using a high entropy strategy to prepare Na 0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe 0.2 Ti 0.1 The positive electrode material of O2 has a calculated configuration entropy of 1.56R, which is a high entropy material. Compared with the unmodified medium entropy material, this material has higher structural stability, thus showing a longer cycle life. At the same time, its electrochemical kinetic performance is optimized due to the high entropy effect, and the ion diffusion coefficient during the charge and discharge process is significantly improved. The material has a lower charge transfer resistance and higher conductivity. Compared with medium entropy transition metal oxide materials with similar molecular formulas, this material exhibits better electrochemical stability.

[0038] 2. The material synthesized by the present invention has uniform particles, good dispersibility and high crystallinity, which is beneficial to improving the stability of the material.

[0039] 3. The material obtained by the present invention has excellent rate performance and stable cycle stability when applied to sodium ion batteries. The preparation method is simple and the raw material cost is low, which makes the material have certain practical application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 SEM image of the layered oxide positive electrode material obtained in Example 1 of the present invention;

[0041] Figure 2 Cycling performance curve of the layered oxide positive electrode material obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0042] Example 1

[0043] A high-entropy iron-manganese-based transition metal layered oxide cathode material Na 0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe 0.2 Ti 0.1 The preparation method of O2 comprises the following steps:

[0044] (1) 0.0053 mol FeSO4·7H2O, 0.0035 mol Fe(NO3)3·9H2O, 0.0054 mol Cu(NO3)2·3H2O, 0.0034 mol CuCl2·2H2O, 0.0074 mol Mn(NO3)2·4H2O, 0.0058 mol MnSO4·H2O, 0.0061 mol Ni(NO3)2·6H2O and 0.0027 mol NiSO4·6H2O were dissolved in 20 mL of an aqueous solution of ethanol and ethylene glycol to prepare a clear light blue first solution; wherein the molar ratio of ethanol, ethylene glycol and water in the aqueous solution of ethanol and ethylene glycol was 0.2:0.2:10, and the concentration of the iron source in the first solution was 0.44 mol / L. 0.06 mol Na2CO3, 0.0033 mol NaHCO3 and 0.0022 mol CH3COONa were dissolved in 30 mL of an aqueous solution of methanol and ethanol to obtain a second solution; wherein, in the aqueous solution of methanol and ethanol, the molar ratio of methanol, ethanol and water was 0.2:0.2:10, and the sodium ion concentration was 4.37 mol / L.

[0045] (2) Pour 100 mL of methanol solution into a three-necked flask and heat it in an oil bath at 60±1°C. The molar ratio of methanol to water in the methanol solution is 0.2:10. While introducing a mixed gas of Ar and H2 with a volume ratio of 19:1 into the three-necked flask, add the first solution and the second solution dropwise at a rate of 500 μL / min, turn on the magnetic stirring, and adjust the pH value of the solution to 8.0. After the solution is added dropwise, stir in an oil bath at 60±1°C for 12 h to obtain an orange-yellow solution.

[0046] (3) The obtained orange-yellow product was aged for 4 h to obtain a uniform particle size, and then the precipitate was collected by high-speed centrifugation at 7000 r / min for 5 min, and washed with deionized water 3 times and anhydrous ethanol 2 times; finally, the precipitate was vacuum dried at 110° C. for 12 h to obtain a precursor, namely, MNCF carbonate precipitate.

[0047] (4) 1 g of the prepared MNCF carbonate precipitate, 0.588 g of NaNO3, 0.147 g of NaCl, 0.067 g of titanium dioxide and 20 mL of an organic solvent were fully mixed and ground, wherein the volume ratio of acetone, ethanol and toluene in the organic solvent was 1:1:0.05, and the mixture was dispersed ultrasonically for 1.5 h and then stirred under strong magnetic stirring for 12 h to obtain a mixture.

[0048] (5) The mixture was transferred into a tube furnace and heated to 500°C at 5°C / min in a mixed gas of N2 and Ar with a volume ratio of 3:1, and kept at this temperature for 4 h, and then heated to 900°C and kept at this temperature for 12 h. After cooling in the furnace, the mixture was quickly ground to obtain a titanium-doped high-entropy layered oxide positive electrode material, which was recorded as Na 0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe 0.2 Ti 0.1 O2, referred to as NMNCFT positive electrode material, its SEM image is as follows Figure 1 shown.

[0049] The obtained product was used as the positive electrode material of sodium ion battery, assembled into CR2025 button-type sodium ion battery in a glove box filled with argon, and charged and discharged in the potential range of 2 to 4.2V. Its cycle performance curve is shown in Figure 2 As shown in Figure 2, at a current of 1C, the first reversible specific capacity is 110 mAh g -1 , the capacity retention rate reached 84.2% after 100 cycles, showing excellent charge and discharge performance and cycle stability.

[0050] Example 2

[0051] A high-entropy iron-manganese-based transition metal layered oxide cathode material Na 0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe 0.2 Ti 0.1 The preparation method of O2 comprises the following steps:

[0052] (1) 0.0046 mol FeSO4·7H2O, 0.0042 mol Fe(NO3)3·9H2O, 0.0044 mol Cu(NO3)2·3H2O, 0.0044 mol CuCl2·2H2O, 0.0072 mol Mn(NO3)2·4H2O, 0.0060 mol MnSO4·H2O, 0.0050 mol Ni(NO3)2·6H2O and 0.0038 mol NiSO4·6H2O were dissolved in 20 mL of an aqueous solution of ethanol and ethylene glycol to prepare a clear light blue first solution; wherein the molar ratio of ethanol, ethylene glycol and water in the aqueous solution of ethanol and ethylene glycol was 0.5:0.4:10, and the concentration of the iron source in the first solution was 0.44 mol / L. 0.06 mol Na2CO3, 0.0016 mol NaHCO3 and 0.0011 mol CH3COONa were dissolved in 30 mL of an aqueous solution of methanol and ethanol to obtain a second solution; wherein, in the aqueous solution of methanol and ethanol, the molar ratio of methanol, ethanol and water was 0.4:0.5:10, and the sodium ion concentration was 4.18 mol / L.

[0053] (2) Pour 100 mL of methanol solution into a three-necked flask and heat it in an oil bath at 60±1°C. The molar ratio of methanol to water in the methanol solution is 0.25:10. While introducing a mixed gas of Ar and H2 with a volume ratio of 29:1 into the three-necked flask, add the first solution and the second solution dropwise at a rate of 400 μL / min, turn on the magnetic stirring, and adjust the pH value of the solution to 8.1. After the solution is added dropwise, stir in an oil bath at 60±1°C for 10 h to obtain an orange-yellow solution.

[0054] (3) The obtained orange-yellow product was aged for 6 h to obtain a uniform particle size, and then the precipitate was collected by high-speed centrifugation at 8000 r / min for 6 min, and washed with deionized water 3 times and anhydrous ethanol 2 times; finally, the precipitate was vacuum dried at 115°C for 14 h to obtain a precursor, namely, MNCF carbonate precipitate.

[0055] (4) 1 g of the prepared MNCF carbonate precipitate, 0.628 g of NaNO3, 0.157 g of NaCl, 0.071 g of titanium dioxide and 20 mL of an organic solvent were thoroughly mixed and ground, wherein the volume ratio of acetone, ethanol and toluene in the organic solvent was 1:1:0.06, and the mixture was dispersed ultrasonically for 2 h and then stirred under strong magnetic stirring for 14 h to obtain a mixture.

[0056] (5) The mixture was transferred into a tube furnace and heated to 400°C at 6°C / min in a mixed gas of N2 and Ar with a volume ratio of 4:1, and kept at this temperature for 4 h, and then heated to 900°C and kept at this temperature for 10 h. After cooling in the furnace, the mixture was quickly ground to obtain a titanium-doped high-entropy layered oxide positive electrode material, which was recorded as Na0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe 0.2 Ti 0.1 O2, referred to as NMNCFT positive electrode material.

[0057] The obtained product was used as the positive electrode material of sodium ion battery, and assembled into CR2025 button-type sodium ion battery in a glove box filled with argon gas, and the charge and discharge cycle was carried out in the potential range of 2 to 4.2V. At a current of 1C, the first reversible specific capacity was 104.6mAh·g -1 , the capacity retention rate reached 90% after 100 cycles, showing excellent charge and discharge performance and cycle stability.

[0058] Example 3

[0059] A high-entropy iron-manganese-based transition metal layered oxide cathode material Na 0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe 0.2 Ti 0.1 The preparation method of O2 comprises the following steps:

[0060] (1) 0.0057 mol FeSO4·7H2O, 0.0031 mol Fe(NO3)3·9H2O, 0.0052 mol Cu(NO3)2·3H2O, 0.0036 mol CuCl2·2H2O, 0.0074 mol Mn(NO3)2·4H2O, 0.0058 mol MnSO4·H2O, 0.0052 mol Ni(NO3)2·6H2O and 0.0036 mol NiSO4·6H2O were dissolved in 20 mL of an aqueous solution of ethanol and ethylene glycol to prepare a clear light blue first solution; wherein the molar ratio of ethanol, ethylene glycol and water in the aqueous solution of ethanol and ethylene glycol was 0.7:1:10, and the concentration of the iron source in the first solution was 0.44 mol / L. 0.065 mol Na2CO3, 0.0015 mol NaHCO3 and 0.001 mol CH3COONa were dissolved in 30 mL of an aqueous solution of methanol and ethanol to obtain a second solution; wherein, in the aqueous solution of methanol and ethanol, the molar ratio of methanol, ethanol and water was 0.5:0.4:10, and the sodium ion concentration was 4.5 mol / L.

[0061] (2) Pour 100 mL of methanol solution into a three-necked flask and heat it in an oil bath at 60±1°C. The molar ratio of methanol to water in the methanol solution is 0.5:10. While passing a mixed gas of Ar and H2 with a volume ratio of 39:1 into the three-necked flask, add the first solution and the second solution dropwise at a rate of 480 μL / min, turn on the magnetic stirring, and adjust the solution pH to 8.2. After the solution is added dropwise, stir in an oil bath at 60±1°C for 14 h to obtain an orange-yellow solution.

[0062] (3) The obtained orange-yellow product was aged for 5 h to obtain a uniform particle size, and then the precipitate was collected by high-speed centrifugation at 9000 r / min for 7 min, and washed with deionized water 3 times and anhydrous ethanol 2 times; finally, the precipitate was vacuum dried at 105°C for 12 h to obtain a precursor, namely, MNCF carbonate precipitate.

[0063] (4) 1 g of the prepared MNCF carbonate precipitate, 0.630 g of NaNO3, 0.105 g of NaCl, 0.067 g of titanium dioxide and 20 mL of an organic solvent were fully mixed and ground, wherein the volume ratio of acetone, ethanol and toluene in the organic solvent was 1:1:0.1, and the mixture was dispersed ultrasonically for 3 h and then stirred under strong magnetic stirring for 9 h to obtain a mixture.

[0064] (5) The mixture was transferred into a tube furnace and heated to 550°C at 8°C / min in a mixed gas of N2 and Ar with a volume ratio of 3.5:1, and kept at this temperature for 5 h, then heated to 850°C and kept at this temperature for 12 h. After cooling in the furnace, the mixture was quickly ground to obtain a titanium-doped high-entropy layered oxide positive electrode material, denoted as Na 0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe 0.2 Ti 0.1 O2, referred to as NMNCFT positive electrode material.

[0065] The obtained product was used as the positive electrode material of sodium ion battery, and assembled into CR2025 button-type sodium ion battery in a glove box filled with argon gas, and the charge and discharge cycle was carried out in the potential range of 2 to 4.2V. At a current of 1C, the first reversible specific capacity was 107.79mAh·g -1 , the capacity retention rate reached 70% after 100 cycles, showing excellent charge and discharge performance and cycle stability.

[0066] Example 4

[0067] A high-entropy iron-manganese-based transition metal layered oxide cathode material Na 0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe 0.2 Ti0.1 The preparation method of O2 comprises the following steps:

[0068] (1) 0.0060 mol FeSO4·7H2O, 0.0028 mol Fe(NO3)3·9H2O, 0.0051 mol Cu(NO3)2·3H2O, 0.0037 mol CuCl2·2H2O, 0.0072 mol Mn(NO3)2·4H2O, 0.0060 mol MnSO4·H2O, 0.0046 mol Ni(NO3)2·6H2O and 0.0042 mol NiSO4·6H2O were dissolved in 20 mL of an aqueous solution of ethanol and ethylene glycol to prepare a clear light blue first solution; wherein the molar ratio of ethanol, ethylene glycol and water in the aqueous solution of ethanol and ethylene glycol was 1:0.7:10, and the concentration of the iron source in the first solution was 0.44 mol / L. 0.06 mol Na2CO3, 0.003 mol NaHCO3 and 0.002 mol CH3COONa were dissolved in 30 mL of an aqueous solution of methanol and ethanol to obtain a second solution; wherein, in the aqueous solution of methanol and ethanol, the molar ratio of methanol, ethanol and water was 0.5:0.6:10, and the sodium ion concentration was 4.33 mol / L.

[0069] (2) Pour 100 mL of methanol solution into a three-necked flask and heat it in an oil bath at 60±1°C. The molar ratio of methanol to water in the methanol solution is 0.3:10. While passing a mixed gas of Ar and H2 at a volume ratio of 49:1 into the three-necked flask, add the first solution and the second solution dropwise at a rate of 200 μL / min, turn on the magnetic stirring, and adjust the solution pH to 8.0. After the solution is added dropwise, stir in an oil bath at 60±1°C for 13 h to obtain an orange-yellow solution.

[0070] (3) The obtained orange-yellow product was aged for 5 h to obtain a uniform particle size, and then the precipitate was collected by high-speed centrifugation at 7500 r / min for 6 min, and washed with deionized water 3 times and anhydrous ethanol 2 times; finally, the precipitate was vacuum dried at 112°C for 17 h to obtain a precursor, namely, MNCF carbonate precipitate.

[0071] (4) 1 g of the prepared MNCF carbonate precipitate, 0.672 g of NaNO3, 0.112 g of NaCl, 0.071 g of titanium dioxide and 20 mL of an organic solvent were thoroughly mixed and ground, wherein the volume ratio of acetone, ethanol and toluene in the organic solvent was 1:1:0.08, and the mixture was dispersed by ultrasonication for 2.5 h and then stirred by strong magnetic stirring for 12 h to obtain a mixture.

[0072] (5) The mixture was transferred into a tube furnace and heated to 400°C at 7°C / min in a mixed gas of N2 and Ar with a volume ratio of 3.8:1, and kept at this temperature for 4.5 h, and then heated to 900°C and kept at this temperature for 13 h. After cooling in the furnace, the mixture was quickly ground to obtain a titanium-doped high-entropy layered oxide positive electrode material, which was recorded as Na 0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe 0.2 Ti 0.1 O2, referred to as NMNCFT positive electrode material.

[0073] The obtained product was used as the positive electrode material of sodium ion battery, and assembled into CR2025 button-type sodium ion battery in a glove box filled with argon gas, and the charge and discharge cycle was carried out in the potential range of 2 to 4.2V. At a current of 1C, the first reversible specific capacity was 103mAh·g -1 , the capacity retention rate reached 83.7% after 100 cycles, showing excellent charge and discharge performance and cycle stability.

[0074] Example 5

[0075] A high-entropy iron-manganese-based transition metal layered oxide cathode material Na 0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe 0.2 Ti 0.1 The preparation method of O2 comprises the following steps:

[0076] (1) 0.0055 mol FeSO4·7H2O, 0.0033 mol Fe(NO3)3·9H2O, 0.0050 mol Cu(NO3)2·3H2O, 0.0038 mol CuCl2·2H2O, 0.0074 mol Mn(NO3)2·4H2O, 0.0058 mol MnSO4·H2O, 0.0047 mol Ni(NO3)2·6H2O and 0.0041 mol NiSO4·6H2O were dissolved in 20 mL of an aqueous solution of ethanol and ethylene glycol to prepare a clear light blue first solution; wherein the molar ratio of ethanol, ethylene glycol and water in the aqueous solution of ethanol and ethylene glycol was 1:1:10, and the concentration of the iron source in the first solution was 0.44 mol / L. 0.06 mol Na2CO3, 0.0015 mol NaHCO3 and 0.001 mol CH3COONa were dissolved in 30 mL of an aqueous solution of methanol and ethanol to obtain a second solution; wherein, in the aqueous solution of methanol and ethanol, the molar ratio of methanol, ethanol and water was 0.6:0.3:10, and the sodium ion concentration was 4.17 mol / L.

[0077] (2) Pour 100 mL of methanol solution into a three-necked flask and heat it in an oil bath at 60±1°C. The molar ratio of methanol to water in the methanol solution is 0.45:10. While passing a mixed gas of Ar and H2 with a volume ratio of 24:1 into the three-necked flask, add the first solution and the second solution dropwise at a rate of 450 μL / min, turn on the magnetic stirring, and adjust the solution pH to 8.2. After the solution is added dropwise, stir in an oil bath at 60±1°C for 12 h to obtain an orange-yellow solution.

[0078] (3) The obtained orange-yellow product was aged for 3 h to obtain a uniform particle size, and then the precipitate was collected by high-speed centrifugation at 9000 r / min for 4 min, and washed with deionized water 3 times and anhydrous ethanol 2 times; finally, the precipitate was vacuum dried at 108°C for 10 h to obtain a precursor, namely, MNCF carbonate precipitate.

[0079] (4) 1 g of the prepared MNCF carbonate precipitate, 0.612 g of NaNO3, 0.153 g of NaCl, 0.069 g of titanium dioxide and 20 mL of an organic solvent were thoroughly mixed and ground, wherein the volume ratio of acetone, ethanol and toluene in the organic solvent was 1:1:0.05, and the mixture was ultrasonically dispersed for 2 h and then strongly magnetically stirred for 12 h to obtain a mixture.

[0080] (5) The mixture was transferred into a tube furnace and heated to 500°C at 5°C / min in a mixed gas of N2 and Ar with a volume ratio of 3.2:1, and kept at this temperature for 4 h, then heated to 850°C and kept at this temperature for 11 h. After cooling in the furnace, the mixture was quickly ground to obtain a titanium-doped high-entropy layered oxide positive electrode material, denoted as Na 0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe 0.2 Ti 0.1 O2, referred to as NMNCFT positive electrode material.

[0081] The obtained product was used as the positive electrode material of sodium ion battery, and assembled into CR2025 button-type sodium ion battery in a glove box filled with argon gas, and the charge and discharge cycle was carried out in the potential range of 2 to 4.2 V. At a current of 1C, the first reversible specific capacity was 106.37 mAh·g -1 , the capacity retention rate reached 78.8% after 100 cycles, showing excellent charge and discharge performance and cycle stability.

[0082] Example 6

[0083] A high-entropy iron-manganese-based transition metal layered oxide cathode material Na 0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe0.2 Ti 0.1 The preparation method of O2 comprises the following steps:

[0084] (1) 0.0044 mol FeSO4·7H2O, 0.0044 mol Fe(NO3)3·9H2O, 0.0052 mol Cu(NO3)2·3H2O, 0.0036 mol CuCl2·2H2O, 0.0071 mol Mn(NO3)2·4H2O, 0.0061 mol MnSO4·H2O, 0.0045 mol Ni(NO3)2·6H2O and 0.0043 mol NiSO4·6H2O were dissolved in 20 mL of an aqueous solution of ethanol and ethylene glycol to prepare a clear light blue first solution; wherein the molar ratio of ethanol, ethylene glycol and water in the aqueous solution of ethanol and ethylene glycol was 0.4:0.5:10, and the concentration of the iron source in the first solution was 0.44 mol / L. Dissolve 0.065 mol Na2CO3, 0.003 mol NaHCO3 and 0.002 mol CH3COONa in 30 mL of an aqueous solution of methanol and ethanol to obtain a second solution; wherein the aqueous solution of methanol and ethanol has a molar ratio of methanol, ethanol and water of 0.2:0.5:10, and a sodium ion concentration of 4.67 mol / L;

[0085] (2) Pour 100 mL of methanol solution into a three-necked flask and heat it in an oil bath at 60±1°C. The molar ratio of methanol to water in the methanol solution is 0.35:10. While passing a mixed gas of Ar and H2 at a volume ratio of 35:1 into the three-necked flask, add the first solution and the second solution dropwise at a rate of 300 μL / min, turn on the magnetic stirring, and adjust the solution pH to 8.1. After the solution is added dropwise, stir in an oil bath at 60±1°C for 12 h to obtain an orange-yellow solution.

[0086] (3) The obtained orange-yellow product was aged for 4 h to obtain a uniform particle size, and the precipitate was collected by high-speed centrifugation at 9000 r / min for 7 min, and washed with deionized water 3 times and anhydrous ethanol 2 times; finally, the precipitate was vacuum dried at 115°C for 16 h to obtain a precursor, namely, MNCF carbonate precipitate.

[0087] (4) 1 g of the prepared MNCF carbonate precipitate, 0.654 g of NaNO3, 0.109 g of NaCl, 0.069 g of titanium dioxide and 20 mL of an organic solvent were fully mixed and ground, wherein the volume ratio of acetone, ethanol and toluene in the organic solvent was 1:1:0.1, and the mixture was dispersed ultrasonically for 1 h and then stirred under strong magnetic stirring for 8 h to obtain a mixture.

[0088] (5) The mixture was transferred into a tube furnace and heated to 500°C at 8°C / min in a mixed gas of N2 and Ar with a volume ratio of 4:1, and kept at this temperature for 5 h, then heated to 900°C and kept at this temperature for 10 h. After cooling in the furnace, the mixture was quickly ground to obtain a titanium-doped high-entropy layered oxide positive electrode material, denoted as Na 0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe 0.2 Ti 0.1 O2, referred to as NMNCFT positive electrode material.

[0089] The obtained product was used as the positive electrode material of sodium ion battery, and assembled into CR2025 button-type sodium ion battery in a glove box filled with argon gas, and the charge and discharge cycle was carried out in the potential range of 2 to 4.2V. At a current of 1C, the first reversible specific capacity was 104.65mAh·g -1 , the capacity retention rate reached 72.77% after 100 cycles, showing excellent charge and discharge performance and cycle stability.

[0090] Example 7

[0091] A high-entropy iron-manganese-based transition metal layered oxide cathode material Na 0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe 0.2 Ti 0.1 The preparation method of O2 comprises the following steps:

[0092] (1) 0.0055 mol FeSO4·7H2O, 0.0033 mol Fe(NO3)3·9H2O, 0.0048 mol Cu(NO3)2·3H2O, 0.0040 mol CuCl2·2H2O, 0.0075 mol Mn(NO3)2·4H2O, 0.0057 mol MnSO4·H2O, 0.0062 mol Ni(NO3)2·6H2O and 0.0026 mol NiSO4·6H2O were dissolved in 20 mL of an aqueous solution of ethanol and ethylene glycol to prepare a clear light blue first solution; wherein the molar ratio of ethanol, ethylene glycol and water in the aqueous solution of ethanol and ethylene glycol was 0.7:0.6:10, and the concentration of the iron source in the first solution was 0.44 mol / L. 0.06 mol Na2CO3, 0.0045 mol NaHCO3 and 0.003 mol CH3COONa were dissolved in 30 mL of an aqueous solution of methanol and ethanol to obtain a second solution; wherein, in the aqueous solution of methanol and ethanol, the molar ratio of methanol, ethanol and water was 0.5:0.2:10, and the sodium ion concentration was 4.5 mol / L.

[0093] (2) Pour 100 mL of methanol solution into a three-necked flask and heat it in an oil bath at 60±1°C. The molar ratio of methanol to water in the methanol solution is 0.4:10. While passing a mixed gas of Ar and H2 with a volume ratio of 45:1 into the three-necked flask, add the first solution and the second solution dropwise at a rate of 500 μL / min, turn on the magnetic stirring, and adjust the solution pH to 8.2. After the solution is added dropwise, stir in an oil bath at 60±1°C for 10 h to obtain an orange-yellow solution.

[0094] (3) The obtained orange-yellow product was aged for 6 h to obtain a uniform particle size, and then the precipitate was collected by high-speed centrifugation at 8000 r / min for 5 min, and washed with deionized water 3 times and anhydrous ethanol 2 times; finally, the precipitate was vacuum dried at 105°C for 18 h to obtain a precursor, namely, MNCF carbonate precipitate.

[0095] (4) 1 g of the prepared MNCF carbonate precipitate, 0.596 g of NaNO3, 0.149 g of NaCl, 0.068 g of titanium dioxide and 20 mL of an organic solvent were fully mixed and ground, wherein the volume ratio of acetone, ethanol and toluene in the organic solvent was 1:1:0.07, and the mixture was dispersed by ultrasonic for 2 h and then stirred by strong magnetic stirring for 12 h to obtain a mixture.

[0096] (5) The mixture was transferred into a tube furnace and heated to 500°C at 5°C / min in a mixed gas of N2 and Ar with a volume ratio of 3:1, and kept at this temperature for 5 h, and then heated to 900°C and kept at this temperature for 12 h. After cooling in the furnace, the mixture was quickly ground to obtain a titanium-doped high-entropy layered oxide positive electrode material, which was recorded as Na 0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe 0.2 Ti 0.1 O2, referred to as NMNCFT positive electrode material.

[0097] The obtained product was used as the positive electrode material of sodium ion battery, and assembled into CR2025 button-type sodium ion battery in a glove box filled with argon gas, and the charge and discharge cycle was carried out in the potential range of 2 to 4.2 V. At a current of 1C, the first reversible specific capacity was 108.92 mAh g -1 , the capacity retention rate reached 72.64% after 100 cycles, showing excellent charge and discharge performance and cycle stability.

[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments or to replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high entropy iron-manganese-based transition metal layered oxide positive electrode material, characterized in that: The following steps are involved: (1) dissolving an iron source, a copper source, a manganese source and a nickel source in an aqueous solution of ethanol and ethylene glycol in a ratio of 2:2:3:2 of the sum of the molar amounts of all components to form a first solution; dissolving a sodium-containing precipitant in an aqueous solution of methanol and ethanol to form a second solution; (2) transferring the methanol solution to a reaction vessel and heating it in an oil bath; setting three ports on the top of the reaction vessel; introducing hydrogen and argon reaction stabilizing protective gas into the first port of the reaction vessel; dripping the first solution into the reaction vessel through the second port; dripping the second solution into the reaction vessel through the third port; turning on magnetic stirring; and adjusting the pH value of the solution at the same time; After the first solution and the second solution are added dropwise, stir under an oil bath to obtain an orange-yellow solution; (3) The obtained orange-yellow solution is allowed to stand for aging, and then centrifuged and solid-liquid separated. The obtained centrifugal precipitate is washed with water and then with anhydrous ethanol; the washed precipitate is vacuum dried at 110±5° C. to obtain a precursor, i.e., MNCF carbonate precipitate; (4) fully mixing and grinding the prepared MNCF carbonate precipitate with a sodium supplement, titanium dioxide and an organic solvent, and performing ultrasonic stirring to obtain a mixture; (5) The mixture in the above step (4) is heated under nitrogen and argon anti-oxidation protective gas, cooled in the furnace and then quickly ground to obtain a titanium-doped high-entropy iron-manganese-based transition metal layered oxide positive electrode material, denoted as Na 0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe 0.2 Ti 0. 1O2.

2. The method for preparing a high entropy iron-manganese-based transition metal layered oxide positive electrode material according to claim 1, characterized in that: In the step (1), the iron source is a mixture of FeSO4·7H2O and Fe(NO3)3·9H2O, and the molar ratio of FeSO4·7H2O to Fe(NO3)3·9H2O is (1-2.15):1; The copper source is a mixture of Cu(NO3)2·3H2O and CuCl2·2H2O, and the molar ratio of Cu(NO3)2·3H2O to CuCl2·2H2O is (1-1.6):1; The manganese source is a mixture of Mn(NO3)2·4H2O and MnSO4·H2O, and the molar ratio of Mn(NO3)2·4H2O to MnSO4·H2O is (1.15-1.32):1; The nickel source is a mixture of Ni(NO3)2·6H2O and NiSO4·6H2O, and the molar ratio of Ni(NO3)2·6H2O to NiSO4·6H2O is (1-2.4):1; The sodium-containing precipitant is a mixture of Na2CO3, NaHCO3 and CH3COONa, and the molar ratio of Na2CO3, NaHCO3 and CH3COONa is (2-6.5): (0.145-0.15): 0.1; the molar ratio of the amount of the sodium-containing precipitant added to the total amount of metal elements added to the iron source, copper source, manganese source and nickel source is (1.55-1.8): 1; The concentration of the iron source in the first solution is 0.44 mol / L, and the concentration of sodium ions in the sodium-containing precipitant in the second solution is 4.15 mol / L to 4.7 mol / L.

3. The method for preparing a high entropy iron-manganese-based transition metal layered oxide positive electrode material according to claim 1, characterized in that: In the step (1), in the aqueous solution of ethanol and ethylene glycol, the molar ratio of ethanol, ethylene glycol and water is (0.2-1): (0.2-1): 10; In the aqueous solution of methanol and ethanol, the molar ratio of methanol, ethanol and water is (0.2-0.6):(0.2-0.6):

10.

4. The method for preparing a high entropy iron-manganese-based transition metal layered oxide positive electrode material according to claim 1, characterized in that: In the step (2), the oil bath temperature is 60±1° C., the stirring time is 10 h to 14 h; the dropping rate of the first solution and the second solution is 200 μL / min to 500 μL / min, and the pH range is 8 to 8.

2.

5. The method for preparing a high entropy iron-manganese-based transition metal layered oxide positive electrode material according to claim 1, characterized in that: In the step (2), the hydrogen-argon reaction stabilizing protective gas is a mixed gas of Ar and H2, and the volume ratio of Ar to H2 is (19-49):1; in the methanol solution, the molar ratio of methanol to water is (0.2-0.5):10; the volume ratio of the first solution, the second solution and the methanol solution is 2:3:10; In the step (3), the orange-yellow solution is allowed to stand for 3 to 6 hours, the centrifugal speed is 7000 to 9000 r / min, and the centrifugal time is 4 to 7 minutes.

6. The method for preparing a high entropy iron-manganese-based transition metal layered oxide positive electrode material according to claim 1, characterized in that: In the step (4), the sodium supplement is a mixture of NaNO3 and NaCl, and the mass ratio of NaNO3 to NaCl is (4-6):1; The mass ratio of the MNCF carbonate precipitate, the sodium supplement and titanium dioxide is (14-15): (10.95-11.1): 1; The organic solvent is a mixture of acetone, ethanol and toluene, and the volume ratio is 1:1:(0.05-0.1).

7. The method for preparing a high entropy iron-manganese-based transition metal layered oxide positive electrode material according to claim 1, characterized in that: In the step (4), the ratio of the total mass of the MNCF carbonate precipitate, the sodium source B and the titanium dioxide to the volume of the organic solvent is (g:L) (90-92.8):1; The ultrasonic stirring is specifically, ultrasonic dispersion for 1 to 3 hours, followed by strong magnetic stirring for 8 to 14 hours.

8. The method for preparing a high entropy iron-manganese-based transition metal layered oxide positive electrode material according to claim 1, characterized in that: In the step (5), the nitrogen-argon anti-oxidation protective gas is a mixed gas of Ar and N2, and the volume ratio of N2 to Ar is (3-4):1; the heating process is specifically: heating to 400-550°C at a heating rate of 5-8°C / min, keeping warm for 4-5h, and then heating to 850-900°C and keeping warm for 10-13h.

9. A high entropy iron-manganese-based transition metal layered oxide positive electrode material, characterized in that: Prepared by the method of claim 1, specifically Na 0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe 0.2 Ti 0.1 O2.

10. The use of a high entropy iron-manganese-based transition metal layered oxide positive electrode material according to claim 9, characterized in that: The following steps are involved: High-entropy Fe-Mn-based transition metal layered oxide cathode materials Na 0.8 Mn 0.3 Ni 0.2 Cu 0.2 Fe 0.2 Ti 0.1 O2 was used as the electrode material of the sodium ion battery and metallic sodium sheets were used as the counter electrode. They were assembled into a CR2025 button-type sodium ion battery in a glove box filled with argon and subjected to charge and discharge cycles in the potential range of 2 to 4.2 V. At a current of 1 C, the first reversible specific capacity was 103 to 110 mAh / g, and the capacity retention rate reached 70% to 90% after 100 cycles.

Citation Information

Cited By

  • Titanium-doped high-nickel layered oxide material, and preparation method and application thereof

    CN122667641A